“EXPLORING THE ROLE OF STEM CELL THERAPIES IN HEMATOLOGIC DISORDERS" - Mahdi Hassan Asiri , Amjad Abdullah Haddad ,Ahmed Mohammed Shtefi , Abdulkhalq Abdullah Alasmari , Nasser Mohammed Ayedh Alrifdh , Salman Mousa Muyidi ,,; Sami Saud Mousa Alharbi ,Abdullah Ibrahim Al-Hussaini ,Yousef Sahoud Maoala Alharbi ,Jamilh Saad Basheer Almutairi, Yasir Hassen Mousa Salhbi, Fahad Ahmad Ali Hakami, (Chelonian Research Foundation, 2022)
This review provides a comprehensive examination of pluripotent stem cells (PSCs) and hematopoietic stem cell transplantation (HSCT) in the context of hematological disorders. It begins by detailing the generation of PSCs, emphasizing the development of reprogramming techniques and the selection of appropriate somatic cell types for induced pluripotent stem cell (iPSC) production. The review highlights the significance of understanding factors affecting reprogramming efficiency and the impact of DNA methylation levels on iPSC differentiation. Moving forward, the review explores the role of PSCs as disease models, demonstrating their utility in elucidating disease mechanisms, drug responses, and therapeutic targets for various hematological disorders. By leveraging patient-specific iPSCs, researchers gain invaluable insights into disease pathogenesis and test novel treatment strategies. Furthermore, the review discusses the evolving landscape of HSCT across different hematological malignancies, including acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloid leukemia (CML), myeloproliferative disorders, myelodysplastic syndromes (MDS), chronic lymphocytic leukemia (CLL), and lymphomas. It examines advancements such as non-T-depleted haploidentical donor HSCT and the use of donor-specific molecular markers for risk assessment. In summary, this review underscores the transformative potential of PSCs in disease modeling, drug discovery, and personalized medicine, alongside the vital role of HSCT as a curative option for various hematological disorders. Through ongoing research and clinical advancements, PSCs and HSCT have the capacity to revolutionize treatment paradigms and enhance outcomes for patients with hematological diseases. Key words: Stem cells, Hematology, Transplantation, pluripotent stem cells, hematopoietic stem cell transplantation.